Peningkatan Peluang Bisnis Strategi Industri Migas Terhadap Pengaruh Pandemi Covid-19 Di Indonesia - Edy Soesanto; Aly Rasyid; Bobby Devagan (Jurnal Bhara Petro Energi, 2022)
The oil as well as fuel market participates in an essential function in the Indonesian economic climate, as an income source APBN as well as a resource of power (particularly gas) towards steer different industries of lifestyle throughout Indonesia. Limitations on individual motion have actually resulted in a straight decrease popular for gas. Along with reducing usage, Covid-19 likewise has actually an effect on reducing oil as well as fuel costs as well as manufacturing, consisting of ceasing upstream tasks as well as decreasing fine-tuning tasks. Within this particular examine, monitorings were actually made from all of upstream oil as well as fuel company tasks in Indonesia particularly, since the effect of the Covid-19 pandemic consisted of the effect of worldwide problems overall, to ensure that healing initiatives could be created in addition to recommendations for handling problems that might intensify. The outcomes of this particular examine end that the avoidance of the effect of Covid-19 for the upstream oil as well as fuel company should be actually performed comprehensively as well as includes all of stakeholders, to ensure that the oil as well as fuel market can easily remain to make it through amidst the direct visibility of the Covid-19 pandemic.